The impact of plantations of Pinus spp. on the chemical properties of soils and stream waters in South African upland catchments - Nowicki, Thomas Edward (University of Cape Town, 2016)
Bibliography: pages 171-181. === Studies of forest ecosystems have indicated that internal sources constitute a significant component of the acid load to forest soils and can result in significant decreases in soil pH, acid neutralising capacity and base status. Despite this, the possibility that these processes can result in a significant transfer of acidity to drainage solutions and consequently to associated surface waters has, to a large extent, been discounted due to the self-limiting nature of " natural" acidification processes which purportedly do not involve significant concentrations of the strong acid anions NO₃⁻, SO₄²⁻ and Cl⁻. In South Africa, extensive plantations of Pinus spp. (pine) are developed in mountainous regions that were previously covered by grassland or fynbos (macchia) vegetation and are mostly not believed to be influenced by significant atmospheric pollution. Thus, a good opportunity exists to study the effects of afforestation without the superimposed influence of acid deposition. This thesis documents the results of a regional investigation of the geochemical impact of pine afforestation in South Africa. The study focuses specifically on factors relating to the transfer of soil acidity to drainage waters. The key questions that are addressed are : 1) to what extent is soil acidification, as previously documented for plantations in the eastern seaboard region of southern Africa, prevalent in other forestry areas within South Africa?; 2) in the absence of acid deposition, can afforestation cause enhanced concentrations of strong acid anions in soil solutions and drainage waters, and can this lead to the transfer of large quantities of acidity from forest soils to surface waters ?; 3) does afforestation-induced acidification lead to increased concentrations of environmentally important metals such as Al and Mn in soil solutions and surface waters ?; and 4) how does afforestation affect the quantity of dissolved organic matter in soils and streams?